Post- versus intra-operative implant for breast cancer interstitial brachytherapy: How to choose? - Gimeno-Morales, Marta; Motisi, Laura; Rodriguez-Spiteri, Natalia; Martínez-Regueira, Fernando; Therapist, Tucker Worthington Radiation; Strnad, Vratislav; Hannoun-Levi, Jean Michel; Gutierrez, Cristina (Journal of Contemporary Brachytherapy, 2024)
Purpose: Breast brachytherapy (BB) represents an important radiation therapy modality in modern breast cancer treatments. Currently, BB is mainly used for accelerated partial breast irradiation (APBI), local boost after whole breast radiation therapy (WBRT), and as salvage re-irradiation after second lumpectomy (APBrl). Two multi-catheter interstitial brachytherapy (MIB) techniques can be offered: intra-operative (IOB) and post-operative (POB) brachytherapy. The aim of this article was to summarize current available data on these two different brachytherapy approaches for breast cancer. Material and methods: A literature search was performed, and different experiences published by BB expert teams were analyzed and compared. These two different brachytherapy approaches for breast cancer have also been presented and discussed during meetings of the GEC-ESTRO BCWG. In addition, expert recommendations were defined. Results: A comprehensive description and practical comparison of both the techniques, i.e., IOB and POB, considering the latest available published data were presented. Different technical, logistic, and clinical aspects of both the methods were thoroughly examined and analyzed. This detailed comparison of the two breast brachytherapy techniques was supported by scientific data from extensive experience of experts, facilitating an objective analysis that, to our knowledge, has not been previously published. Conclusions: Based on the comprehensive analysis of both the brachytherapy techniques available, this article serves as a valuable resource to guide breast teams in selecting the optimal BB technique (POB or IOB), considering hospital environment, multi-disciplinary collaboration, and patient logistics.
CRIS-Team Scopus Importer:2024-05-03
Keywords: accelerated partial breast irradiation; brachytherapy; breast cancer; intra-operative brachytherapy; post-operative brachytherapy